Value at Risk at Asian Emerging Stock Markets - Syed Muhammad Waqar Azeem Naqvi; Syed Kumail Abbas Rizvi; Orangzab; Muhammad Ali (Science International, 2016)
This study tries to calculate value at risk at Asian emerging stock markets of daily, weekly and monthly stock returns by calculating its log returns. This study also ranks equity markets on the basis on Sharpe ratio and risk adjusted returns. This process helps investors to gauge these stock markets on various risk levels present in these market to make a good decision of investment for wealth maximization. This study uses 10 year financial data from 2004 to 2014 of daily weekly and monthly data frequency. Value at risk is calculate of all data frequencies at 1 and 5 percent level of significance. Results are different in short, medium and relatively long run cases of each stock market. However, collectively, Pakistan, Indian and Malaysian markets perform better at a given level of risk and return.
Keywords: G10; G11; 330; Risk; Return; Value at Risk; Emerging Markets